2011
DOI: 10.1002/ejoc.201100238
|View full text |Cite
|
Sign up to set email alerts
|

C–H Bond Functionalization of Arylpyrimidines Catalyzed by an in situ Generated Ruthenium(II) Carboxylate System and the Construction of Tris(heteroaryl)‐Substituted Benzenes

Abstract: A ruthenium(II) carboxylate catalyst, generated in situ from [RuCl 2 (p-cymene)] 2 and 1-phenyl-1-cyclopentanecarboxylic acid (PCCA) in the presence of K 2 CO 3 , allowed activation of the C-H bond in phenyl-substituted pyrimidines and their direct functionalization with both electron-deficient and elec-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 68 publications
0
20
0
Order By: Relevance
“…2-Arylpyrimidines have been arylated using Ru(II)catalysis. 8 Moreover, 5-membered ring N-heterocycles such as pyrazoles (III), 6b, 6c tetrazoles (IV), 9 benzoxazoles, 10 benzothiazoles, 11 and (benzo)imidazoles (V), 7b, 12 have been successfully used as directing groups in Pd-catalyzed C-H bond arylation. One of the major advantage to employ heterocycles as directing group is that they can be an integral part of the target final structure or did not required additional step to be removed.…”
Section: Quinoxaline As Integrated Directing Group In Palladium-catalmentioning
confidence: 99%
“…2-Arylpyrimidines have been arylated using Ru(II)catalysis. 8 Moreover, 5-membered ring N-heterocycles such as pyrazoles (III), 6b, 6c tetrazoles (IV), 9 benzoxazoles, 10 benzothiazoles, 11 and (benzo)imidazoles (V), 7b, 12 have been successfully used as directing groups in Pd-catalyzed C-H bond arylation. One of the major advantage to employ heterocycles as directing group is that they can be an integral part of the target final structure or did not required additional step to be removed.…”
Section: Quinoxaline As Integrated Directing Group In Palladium-catalmentioning
confidence: 99%
“…A great number of them are based on nitrogen as the metal-coordinating atom, the pyridine ring being prevalent, although other azaheterocycles, such as pyrazole, oxazoline, and quinoline have also been successfully employed in transition-metal-catalyzed ortho-C-H bond functionalization [33]. Požgan and co-workers have demonstrated that the quinazolinyl [34,35] and pyrimidinyl [36] groups efficiently allow regioselective ortho-arylations in the presence of Ru(II)-carboxylate catalyst, even in water as the solvent in some cases [37,38]. The success of Ru(II) catalysts is most likely ascribed to the easy formation of ruthenacyclic intermediate stable in water via C-H bond deprotonation with the assistance of directing groups [35,37,[39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, many synthetic methods for the construction of pyrazine derivatives have been developed [58][59][60][61][62][63], yet there is still great demand for the generation of novel pyrazine libraries. As a part of our ongoing interest in metal-catalyzed functionalization of (hetero)arenes via C-H bond activation [34][35][36][37][38], we reasoned that a pyrazine nucleus could direct cleavage and further functionalization of ortho-C-H bonds of the benzene ring in phenyl-substituted pyrazines. Moreover, by using 2,3-diphenylpyrazines as substrates, both nitrogen atoms could cooperate with the catalytic metal center to hypothetically promote four ortho-C-H bond activations, thus enabling the construction of highly functionalized, especially arylated or π-conjugated pyrazine derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we reported a successful Ru II ‐catalyzed arylation of phenylpyrimidines in the presence of 1‐phenyl‐1‐cyclopentanecarboxylic acid as the carboxylate ligand and extended the methodology for 2‐substituted quinazoline derivatives …”
Section: Introductionmentioning
confidence: 99%